Modeling of Oxidation Kinetics in Air of Steel-T21 Alloy Coated by Simultaneous Germanium-Doped Aluminizing Silicon zing Process - Hussein, Abbas Kh. (Nahrain University College of Engineering Journal, 2008)
This work includes the application of a pack cementation of germanium-doped aluminum and silicon coatings on low alloy steel type- T21 yields a significant improvement in the oxidation. Steel-T21 was coated with germanium-doped aluminzing-siliconizing. Diffusion coating was carried out at 1050 oC for 6 h under an Ar atmosphere by simultaneous germanium-dopded aluminizingsiliconizing process. Cyclic oxidation tests were conducted on the coated steel-T21 alloyin the temperature range oxide 600-800 oC in air for 30 h at 5 h cycle. The results showed that the oxidation kinetics for coated system in air was found to be parabolic .Oxide phases that formed on coated system are SiO2 and Cr2O3..Mthamatical model using MATLAB show that there is multiple linear model foroxidation kinetics.